ANALYSIS OF THE COORDINATION OF THE 20 KV SYSTEM PROTECTION ON THE 30 MVA 150/20 KV TOWN FEEDER TRANSFORMER AT THE 150KV SURALAYA SUBSTATION - Kajat Sartono; Martin Djamin; Suryadi Suryadi (Jurnal Ilmiah METADATA, 2026)
One type of protective relay that requires coordination in an electric power system is the overcurrent relay (OCR) and ground fault relay (GFR). The OCR/GFR function is crucial for protecting equipment in a substation from short circuits between phases or phase-to-ground faults. Therefore, setting the OCR/GFR relay requires careful and precise calculations to ensure a sensitive, selective, fast, and reliable power protection system. Observations of faults at several substations in the Cilegon Technical Implementation Unit (UPT) revealed discrepancies in the OCR/GFR coordination. The method used was to calculate the OCR/GFR setting values on the feeder side and the main transformer side to analyze the protection system coordination.